Inhibition of T Helper Cell Type 2 Cell Differentiation and Immunoglobulin E Response by Ligand-Activated Vα14 Natural Killer T Cells - Cui, Junqing (The Rockefeller University Press, 1999)
Murine Vα14 natural killer T (NKT) cells are thought to play a crucial role in various immune responses, including infectious, allergic, and autoimmune diseases. Because Vα14 NKT cells produce large amounts of both interleukin (IL)-4 and interferon (IFN)-γ upon in vivo stimulation with a specific ligand, α-galactosylceramide (α-GalCer), or after treatment with anti-CD3 antibody, a regulatory role on helper T (Th) cell differentiation has been proposed for these cells. However, the identity of the cytokine produced by Vα14 NKT cells that play a dominant role on the Th cell differentiation still remains controversial. Here, we demonstrate by using Vα14 NKT-deficient mice that Vα14 NKT cells are dispensable for the induction of antigen-specific immunoglobulin (Ig)E responses induced by ovalbumin immunization or Nippostrongylus brasiliensis infection. However, upon in vivo activation with α-GalCer, Vα14 NKT cells are found to suppress antigen-specific IgE production. The suppression appeared to be IgE specific, and was not detected in either Vα14 NKT– or IFN-γ–deficient mice. Consistent with these results, we also found that ligand-activated Vα14 NKT cells inhibited Th2 cell differentiation in an in vitro induction culture system. Thus, it is likely that activated Vα14 NKT cells exert a potent inhibitory effect on Th2 cell differentiation and subsequent IgE production by producing a large amount of IFN-γ. In marked contrast, our studies have revealed that IL-4 produced by Vα14 NKT cells has only a minor effect on Th2 cell differentiation.